UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MATA PELAJARAN IPS MELALUI METODE INDEX CARD MATCH DI KELAS 7A PADA SMP NEGERI 1 ANGGANA - NURHANIAH NURHANIAH (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2023)
This research aims to improve the activities and learning outcomes of students in social studies subjects through the Index Card Match method in class 7A at SMP Negeri 1 Anggana. This research is classroom action research using the Index Card Match method. The subjects of this research were class 7A students at SMP Negeri 1 Anggana for the 2022/2023 academic year with the number of class 7A students being 33 students consisting of 18 boys and 15 girls. Data collection techniques use observation sheets, written tests and documentation. Data analysis techniques use observation, data reduction, data presentation, and drawing conclusions. Based on discussion and data analysis, it is proven that the application of learning using Index Card Match cards can improve learning outcomes in social studies subjects on the life of Indonesian society during the Praaksara, Hindu, Buddhist and Islamic periods for students in class 7A of SMP Negeri 1 Anggana. This can be seen from the results of data analysis, namely in cycle I the students who achieved completeness were 12 with a percentage of 36.36%, while the students whose grades had not yet reached completeness were 21 students with a percentage of 63.63%. In cycle II, it can be seen from the average of the students' tests that 33 students achieved completeness with a percentage of 100% complete with a completeness score of 85.52%. ABSTRAKPenelitian ini bertujuan untuk meningkatkan aktivitas dan hasil belajar siswa mata pelajaran IPS melalui metode Index Card Match di kelas 7A pada SMP Negeri 1 Anggana. Penelitian ini merupakan penelitian tindakan kelas dengan penerapan metode Index Card Match. Subyek penelitian ini adalah siswa kelas 7A SMP Negeri 1 Anggana tahun pelajaran 2022/2023 dengan jumlah siswa kelas 7A yakni 33 orang siswa yang terdiri dari 18 orang anak laki-laki dan 15 orang anak perempuan. Teknik pengumpulan data menggunakan lembar observasi, tes tulis dan dokumentasi. Teknik analisis data menggunakan pengamatan, reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan pembahasan dan analisis data membuktikan bahwa penerapan pembelajaran menggunakan kartu Index Card Match dapat meningkatkan hasil belajar pada mata pelajaran IPS materi kehidupan masyarakat Indonesia pada Masa Praaksara, Hindu Budha dan Islam pada peserta didik kelas 7A SMP Negeri 1 Anggana. Hal ini dapat dilihat dari hasil analisis data yaitu Pada siklus I siswa yang mencapai ketuntasan 12 dengan persentase 36,36%, sedangkan siswa yang nilainya belum mencapai ketuntasan sebanyak 21 siswa dengan persentase 63,63 %. Pada siklus II dilihat dari rata-rata tes siswa adalah siswa yang mencapai ketuntasan 33 siswa dengan persentase 100% tuntas dengan nilai ketuntasan 85,52%.